PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KABUPATEN BIREUEN - Mursalin, Khairul; Kamaruddin, Kamaruddin (IndOmera, 2021)
The research was conducted on employees of the Education, Youth and Sports Office of Bireuen Regency 1). Knowing the influence of leadership on employee performance, 2). Knowing the effect of communication on employee performance, 3). Knowing how the influence of work discipline on employee performance, and 4). Knowing the influence of leadership, communication and work discipline on the performance of the employees of the Education, Youth and Sports Office of Bireuen Regency. This research is a quantitative research with a survey of 78 employees with data collection through questionnaires. And the method of data analysis with statistics with a path analysis approach. The results showed that a) There is a direct and indirect effect of leadership on employee performance by 18.85%. b) There is a direct and indirect effect of communication on employee performance by 21.04%. c) There is a direct and indirect effect of work discipline on employee performance by 23.5%. Based on the size of the determination coefficient of 0.657, it explains that the contribution of the aspects of leadership, communication and work discipline to employee performance is 65.7%. While the rest (residual value) of the role of the variables not examined was 34.3%, indicating that there are other factors that can affect the performance variable